The effect of product diversification on purchasing decisions at Mandau Bakery Kota Duri Store - Eva Sundari; Iyoyo Dianto; Hamsal Hamsal; Imam Hanafi (Global Academy of Multidisciplinary Studies, 2024)
Purpose: This research aims to analyze the effect of product diversification on purchasing decisions at the Mandau Bakery Shop, Duri City, which based on survey results shows that with product diversification more consumers buy. However, with increasing competition, the Mandau Bakery cake shop experienced ups and downs in the number of consumers. Research Methodology: The method used is descriptive and quantitative, with a simple linear regression test and hypothesis testing using SPSS 21. Data was collected through a questionnaire from 95 respondents who came from consumers who had purchased at the Mandau Bakery shop and were selected using a purposive sampling technique. Results: The research results show that product diversification has a significant effect on consumer purchasing decisions. Conclusions: The study concludes that well-implemented product diversification enhances consumer satisfaction and purchase decisions at Mandau Bakery. Therefore, continuous product innovation and differentiation are vital strategies for sustaining competitiveness in the bakery industry. Limitations: However, this study has limitations, such as limited sample size and research locations only in one place, so the results may not be generalizable. Contribution: This research provides a practical contribution to the management of the Mandau Bakery Store in understanding the importance of product diversification to improve consumer purchasing decisions and enriches academic literature on retail marketing and consumer behavior in the bakery industry.